ผลของโปรแกรมส่งเสริมการแสวงหาความท้าทายในการเรียนรู้ภาษาอังกฤษตามทฤษฎีกรอบความคิดของนักศึกษาระดับปริญญาบัณฑิต - เจนจิรา จาติเทศะ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were to examine the effects of the program to promote challenge-seeking in learning English language based on the mindset theory of undergraduate students. The participants of this study are fourth year undergraduate students from a private University. The method is a true experimental research design, 39 students were randomly assigned into 19 experimental group students and 20 control group students. Instruments included program to promote challenge-seeking in learning English Language based on the mindset theory and the challenge- seeking in learning English language scale. Data were analyzed by Mean, Standard deviation, One-way repeated measures ANOVA and T- Test. Findings were (1) Experimental group students significantly gained higher post-test and delayed post-test scores of challenge-seeking in learning English language than their pre-test scores at .05 level (M post-test = 4.16, SD post-test = 0.45, M delayed post-test = 4.09, SD delayed post-test = 0.46, F = 11.67, p = .00) and the effect size for this analysis was of 1.88 (2) After receiving the program from post-test and delayed post-test, experimental group students gained higher challenge - seeking in learning English language scores than those of a control group at the .05 significance level (Post-test M experimental group = 4.16, SD experimental group = 0.45, M control group = 3.37, SD control group = 0.19, t = 7.13, p = .00 and Delayed post-test M experimental group = 4.09, SD experimental group = 0.46, M control group = 3.32, SD control group = 0.20, t = 6.73, p =.00) and the effect size for this analysis were of 2.29 and 2.17 accordingly.